2021
DOI: 10.30996/persona.v10i1.4502
|View full text |Cite
|
Sign up to set email alerts
|

Stres akademik sebagai mediator antara kesiapan belajar dan kepuasan mahasiswa terhadap proses belajar daring

Abstract: The learning and teaching process has been transformed into an online learning system due to COVID-19, which affected lecturer and university students. This research investigates students online learning satisfaction amid COVID-19 by focusing on online learning readiness and academic stress toward online learning satisfaction. Approximately 276 bachelor’s students (Mage = 20.36, SD = 2.47) hired using the accidental sampling technique participated in this study from public and private universities. The data wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
1
0
2
Order By: Relevance
“…Individual readiness consists of physical and psychological readiness. Good physical and psychological readiness during online learning will facilitate the smooth progress of online chemistry learning, allowing students to receive the material effectively (Akmal & Kumalasari, 2021). The results showed that the average scores for physical readiness and psychological readiness were 3.29 and 3.54, respectively.…”
Section: Influence Of Learning Interest On Learning Readiness Of Stud...mentioning
confidence: 99%
“…Individual readiness consists of physical and psychological readiness. Good physical and psychological readiness during online learning will facilitate the smooth progress of online chemistry learning, allowing students to receive the material effectively (Akmal & Kumalasari, 2021). The results showed that the average scores for physical readiness and psychological readiness were 3.29 and 3.54, respectively.…”
Section: Influence Of Learning Interest On Learning Readiness Of Stud...mentioning
confidence: 99%
“…Sistem pembelajaran dalam jaringan memiliki dampak negatif dimana tidak semua peserta didik memiliki tingkat pemahaman yang sama (Rosyidiana, 2021;Santika, 2020). Bagi peserta didik yang rajin dan mudah menyerap informasi maka cara belajar dalam jaringan akan dengan mudah diserap, namun bagi peserta didik yang kurang terbiasa dengan cara belajar dalam jaringan, kemungkinan akan kesulitan, tidak hanya menyerap perkuliahan berbasisdalam jaringan yang disampaikan dosennya tetapi juga kemampuan beradaptasi dengan aplikasi teknologi yang digunakan dalam kegiatan belajar mengajar (KBM) (Akmal et al, 2021;Santika, 2020;Wulandari et al, 2020). Artinya bagaimanapun canggihnya teknologi yang digunakan belum mampu menggantikan pelaksanaan pembelajaran tatap muka karena metode interaksi tatap muka konvensional masih jauh lebih efektif dibandingkan pembelajaran online atau e-learning (Khamim, 2021;Ritonga et al, 2020).…”
Section: Pendahuluanunclassified
“…Berkaitan dengan temuan penelitian yang kedua bahwa ada perbedaan tingkat stres mahasiswa berdasarkan jenis kelamin. Jenis kelamin dan latar belakang memiliki hubungan yang signifikan dengan tingkat stres akademik, sedangkan usia dan tingkat mahasiswa tidak memiliki hubungan yang signifikan dengan tingkat stres akademik (Akmal & Kumalasari, 2021;Murdhiono et al, 2021). Kepada pembuat kebijakan dan Pemerintah untuk merencanakan intervensi manajemen stres kepada mahasiswa S1 di Indonesia.…”
Section: Pembahasanunclassified